DESKRIPSI KEMAMPUAN MENYELESAIKAN MASALAH SPASIAL SISWA SMP BERDASARKAN GAYA KOGNITIF IMPULSIF DAN REFLEKTIF: Description of Spatial Problem Solving Ability of Junior High School Students Based on Impulsive and Reflective Cognitive Styles - Jaelani, Abd Kadir; Arriah, Fathrul; Ilhamuddin, Ilhamuddin; Baharullah, Baharullah; Syamsuadi, Ahmad (Universitas Tadulako, 2023)
The purpose of this study was to describe the spatial abilities of junior high school students based on impulsive and reflective cognitive styles. This research is a type of descriptive qualitative research. The instruments used in this study are: MFFT (Matching Familiar Figures Test) test to determine students' cognitive styles. Furthermore, 1 impulsive cognitive style subject and 1 reflective cognitive style subject were found. Then both subjects were given spatial ability tests to determine students' spatial abilities after which interviews were conducted. Indicators of spatial ability, namely: (1) state the position of the elements of a spatial construct., (2) construct and present geometric models drawn on a flat plane in the context of space., (3) imagine the shape or position of a geometric object viewed from a certain point of view., (4) investigate the actual size of the visual stimulus of a geometric object. The results showed that students who were cognitively impulsive had low spatial abilities because they were only able to meet 1 indicator of spatial ability, namely constructing and presenting geometric models drawn on a flat plane in the context of space. While students who are cognitively reflective have high spatial abilities because they are able to meet all indicators of spatial ability.